Female‐biased obligate strategies in a partially migratory population. (31st January 2013) - Fudickar, Adam M.; Schmidt, Andreas; Hau, Michaela; Quetting, Michael; Partecke, Jesko
Summary: Partial migration occurs when a breeding population consists of seasonal migrants and year‐round residents. Although it is common among birds, the basis of individual movement decisions within partially migratory populations is still unresolved. Over 4 years, we used state of the art tracking techniques, a combination of geolocators and radio transmitters, to follow individual European blackbirds Turdus merula year round from a partially migratory population to determine individual strategies and departure and arrival dates. The individual‐based tracking combined with measures of energetic and hormonal (corticosterone) state enabled us to distinguish between obligate and facultative migration and to test several classical hypotheses of partial migration: the 'Arrival Time'‐, 'Dominance'‐ and 'Thermal Tolerance'‐hypotheses. Two distinct periods of departures from the breeding grounds were observed during the study; one in early autumn, and another during the midst of winter. Although blackbirds that migrated in autumn were never observed overwintering within 300 km of the study site, four individuals that departed in the winter were observed within 40 km. Females were significantly more likely to migrate in autumn than males but there was no difference in the age or body size of migrants and non migrants in autumn. Just prior to autumn migration, migrants had higher fat scores than non migrants and tended to have higher concentrations of baseline corticosterone, but similar concentrations of triglycerides. Unlike autumn migrants, we found no difference between the tendencies of males versus females to depart in winter, nor did we find any difference in body size or age of individuals that departed in the winter. Autumn migration was sex biased and resembled obligate migration. Our results provide strong support for the 'Arrival Time' hypothesis for partial migration in the autumn. We found no clear support for the 'Dominance' or 'Thermal Tolerance' hypotheses. By tracking individuals year round, we were able to identify a second period of departures. Overall, these results suggest the co‐occurrence of obligate autumn migrants, winter movements and sedentary individuals within a single population. Abstract : Using state‐of‐the‐art tracking techniques to observe the movements of individuals from a partially migratory songbird population year‐round in combination with measures of hormonal and energetic state, we provide the most detailed picture of partial migration in a free‐living population.